Enantioselective synthesis of (+)-(S,S)-reboxetine - Siddiqui, Shafi A.; Narkhede, Umesh C.; Lahoti, Rajgopal J.; Srinivasan, Kumar V. (Synlett, 2006)
An efficient enantioselective synthesis leading directly to (+)-(S,S)-reboxetine has been described from commercially available trans-cinnammyl bromide using Sharpless asymmetric dihydroxylation as the key step.
Keywords: coupling; Dihydroxylation; Hydrogenation; reboxetine; trans-cinnamyl bromide

Efficient synthesis of 1,8-dioxo-octahydro-xanthene derivatives promoted by a room temperature ionic liquid at ambient conditions under ultrasound irradiation - Venkatesan, K.; Pujari, Suresh S.; Lahoti, Rajgopal J.; Srinivasan, K. V. (Ultrasonics Sonochemistry, 2008)
The condensation reaction involving an aldehyde and diketone was efficiently promoted by the Ionic liquid, [Hbim]BF(4) (IL) as a reaction medium with methanol as co-solvent at ambient temperature under ultrasonic irradiation to afford the corresponding 1,8-dioxo-octahydroxantliene (xanthene) derivatives in excellent yields. The advantages of this method include among others the use of a recyclable, non-volatile ionic liquid, which promotes this protocol under ambient temperature without the requirement of ally added catalyst. The reaction times and yields are compared with p-TSA catalyzed synthesis of xanthenes under thermal conditions, which is also reported for the first time under our reaction conditions. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: aldehydes; ambient conditions; Bronsted acidity; dimedone; Ionic liquid; Ultrasound; Xanthenes